2010
DOI: 10.1007/s11292-010-9109-1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of school-based programs to reduce bullying: a systematic and meta-analytic review

Abstract: This article presents a systematic review and meta-analysis of the effectiveness of anti-bullying programs in schools. Studies were included if they evaluated the effects of an anti-bullying program by comparing an intervention group who received the program with a control group who did not. Four types of research design were included: a) randomized experiments, b) intervention-control comparisons with before-and-after measures of bullying, c) other interventioncontrol comparisons, and d) age-cohort designs. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
964
9
124

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,309 publications
(1,133 citation statements)
references
References 71 publications
36
964
9
124
Order By: Relevance
“…Even more important, however, seems to be parents' role in teaching their offspring to regulate their negative emotions and to solve conflicts in a constructive and peaceful manner in order to avoid chronic peer relation difficulties. Together, the present results thus support the notion that parent training as well child-focused activities in current school-based prevention programs are key features for decreasing peer victimization over the long term (Ttofi & Farrington, 2011). Note.…”
Section: Predictors Of Peer Victimization Trajectories 26supporting
confidence: 83%
“…Even more important, however, seems to be parents' role in teaching their offspring to regulate their negative emotions and to solve conflicts in a constructive and peaceful manner in order to avoid chronic peer relation difficulties. Together, the present results thus support the notion that parent training as well child-focused activities in current school-based prevention programs are key features for decreasing peer victimization over the long term (Ttofi & Farrington, 2011). Note.…”
Section: Predictors Of Peer Victimization Trajectories 26supporting
confidence: 83%
“…[24][25][26][27] Most acts of aggression practiced in the school context under investigation were verbal, which suggests an apparent contradiction with the data related to sex, as boys are expected to engage more in physical attacks, while girls are expected to practice more verbal aggressions. 28 Nevertheless, this information may be interpreted in line with the proposals put forward in another Brazilian study 5 , which identified a prevalence of verbal aggressions independently from the aggressors' sex, as the school authorities generally interpret these as less serious and, therefore, less subject to severe punishment.…”
Section: Discussionmentioning
confidence: 65%
“…These studies also signal that measures to prevent, cope with and control bullying in the school contexts need to be taken, considering its personal and contextual (micro and macro) determinants, through the convergence of intersectoral efforts, with a view to addressing the problem at the complexity level it presents. 3,5,15,24 The investigated students' age, for victims as well as for aggressors, was concentrated around the age of 13-14 years, going against the consensus found in the literature which admits the existence of peaks of vulnerability to bullying at moments of transition in teaching. In the Brazilian reality, these correspond to the sixth year of basic education and the first year of secondary education, when students generally are 11 and 15 years old, respectively.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Recommended are multicomponent schoolwide programs based on the SocialEcological Diathesis-Stress Model, 17 which emphasizes the dynamic and fluid nature of bullying across the individual, family, peer group, school and community contexts. [30][31][32] For instance, the Cyber Friendly Schools Program 33,34 is an online whole-school cyberbullying prevention and intervention program built on a social-ecological approach; it reported a significant decline in CV perpetration at one year in a group randomized controlled trial. 35 From a legal perspective, in Canada, cyberbullying can be addressed under civil law or criminal law.…”
Section: Cyberbullying and Health Outcomesmentioning
confidence: 99%